Láser en odontología - Guzmán de Suárez, Beatriz (Revista Estomatología, 1991)
The term Laser means light amplified by stimulated emmiting radiation. It has been used for the last 30 years in different medical areas, including dentistry. Basically it transfers an external energy in lightning or luminic energy. There are two types of laser: surgical and therapeutic. The biological reactions of the different tissues, depend on their optical qualities. In dentistry, it has been used in endodontics to clean seal accesory canals; in operative dentistry; as analgesic, antiinflamatory in surgical procedures. Taking into account the cautions recommended, it offers a good choice oftreatmant for our patients.